‘And the system fails us all the time’: Responses to domestic violence against First Nations women in Australia and the case for an integrated rights-based approach founded in self-determination - Buxton-Namisnyk, E (2022)
First Nations women in Australia experience domestic violence disproportionately compared to Australia’s ‘settler’ population. Prior research suggests that domestic violence responses developed with the ‘settler’ population in mind may be problematic for First Nations women, but to date no studies have examined First Nations women’s domestic violence service interactions prior to fatal violence. I accordingly review a whole-of-population sample of domestic violence-related homicide cases from several Australian jurisdictions, alongside findings from yarning and interviews with First Nations Elders, specialist domestic violence workers and survivors, to examine and analyse First Nations women’s service contact histories preceding fatal violence. Viewing findings from a postcolonial, intersectional perspective attuned to Australia’s history of invasion/colonisation and the ongoing violence of ‘settler’ occupation, I argue the domestic violence response system—comprising criminal justice and specialist service responses—is an expression of colonising state power.